Why several truths can be true - Eivind Meland; John Brodersen (Taylor & Francis Group, 2016)
In this paper, we offer a perspective on complementarity, acknowledging that it is not possible for human perception and cognition to grasp reality with unambiguous concepts or theories. Therefore, multiple concepts and perspectives are valid when they are not exaggerated beyond reasonable limits and do not claim exclusive validity. We recommend a humble stance enabling respectful dialogue between different perspectives in medical science and practice.KEY POINTS No single perspective in clinical or scientific medicine can exhaustively explain medical phenomena. Scientific attitude is characterised by a willingness to look for objections against what we prefer as truths. Complementarity or unifying contradictions are concepts that allow for humility and pluralism in clinical and scientific medicine.